Selection, Consumption, and New Music Exploration in an Online Social Network: A Dyadic Approach - Johannes Loh (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study peer influence in an online social network on a platform where consumers purchase music albums. They can follow their peers and become informed about their consumption choices. In particular, we are interested in how this affects consumers' exploration of new music that exhibits unfamiliar attributes (e.g. artist, genre, or instrumentation). Our empirical analysis contains two parts: First, we analyze how the formation of new dyads in the network depends on consumer-peer similarities in their preference for certain album attributes. This affects music exploration because it determines which peer purchases consumers are exposed to. Second, conditional on the determinants of dyad formation, we investigate how within-dyad information flows affect consumers' purchase decisions, and in particular their exploration of unfamiliar attributes. Our analysis produces three key findings: First, preference similarities between consumers and peers are the strongest predictor of the formation of dyads. This likely stifles consumers' exploration of new music because it limits their exposure to unfamiliar attributes. Second, we find a strong positive peer effect of consumers observing peer purchases after the formation of a dyad. Third, this effect is stronger for albums from unfamiliar artists, but weaker for those that exhibit unfamiliar horizontal attributes (e.g. its genre). Together, this suggests that new music exploration in online social networks is limited and subject to nuance.
Keywords: D12; D83; L82; L86; 330; online social networks; consumption choices; peer influence; music consumption